Menggali Teori dan Efektivitas Gaya Kepemimpinan bagi Generasi Milenial - Intan Palupi, Nur Wulan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to explore relevant leadership theories and assess the effectiveness of leadership styles in the context of the millennial generation, currently the largest cohort in the global workforce. Millennials, who are known to have unique characteristics such as high digital literacy, a need for work-life balance, and a preference for participative and transformational leadership styles, demand different leadership approaches from previous generations. Through the literature study method, this research examines various leadership theories, including transformational, democratic, servant, laissez-faire, and transactional leadership, and how these theories are applied in leading millennials. The results show that transformational and democratic leadership are highly effective in motivating and improving millennial performance, while servant leadership style also contributes positively to employee well-being and loyalty. On the other hand, laissez-faire and transactional leadership tend to be less effective in meeting the needs and expectations of millennials, who value meaning and innovation in their work more. The research concludes that leaders in the modern era need to adopt a more flexible, inclusive and individual development-focused approach to effectively manage and motivate millennials. Strategic recommendations are provided to assist leaders in creating a productive and sustainable work environment for millennials in various sectors.